Are the "boys" at Pixar afraid of little girls? - Ebrahim, Haseenah (Journal of Film and Video, 2015)
The notion that American animated films are somehow excluded from ideological concerns, that they are “ideologically empty,” so to speak, reflects a widespread perception within both the USA and South Africa that children’s films are just innocent, escapist, fun. Walt Disney himself was known to perpetuate this perception by, somewhat disingenuously, remarking that “we just make the pictures, and let the professors tell us what they mean” (quoted in Bell, Haas and Sells 1). Although sometimes tongue-in-cheek, I examine Pixar’s construction of little girls within the context of a brand image of Pixar’s animator-directors as “boys at heart”--that is, as Peter Pan types who have never really grown up. I explore whether Pixar’s films reflect a certain apprehension about little girls that can, perhaps, be likened to the way young boys often display a notable ambivalence toward girls. Pixar’s little girls—Hannah, Molly, Boo, Darla and Bonnie and Daisy—are not always so “sugar and spice and everything nice,” but rather embody toxicity to varying degrees (though not always seriously), becoming a source of fear, pain, or humiliation to a number of male characters in several Pixar films. What initially appears to suggest an aversion to little girls emerges as a more complex construction of little girls by the “boys” at Pixar.
Keywords: Pixar; Animation; Girls; Representation; Boys